Studi Penafsiran Surat Al-Isra’ Ayat 23-24 Tentang Pendidikan Birru al-Walidain - Rizki Dwi Oktavia; Rofi’atul Afifah; Aning Zainun Qoni’ah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
Birrul Walidain education is one of the most important factors in ideal character education. The creation of a generation that has good character is a dream for parents to their children. Birrul walidain education is very influential on adab to parents. In the Qur'an, Allah SWT has explained many verses related to Birrul Walidain. Allah tells the story of a mother's struggle so that a child can know the struggle of a mother so that she can repay him by being kind to him and not being disobedient to him, even if one of them is not to say